A model-updating approach based on the component mode synthesis method and perturbation analysis. (27th October 2018) - Wang, T.; He, H.; Yan, W.; Chen, G.P.
Abstract: A model-updating approach based on an improved free-interface component mode synthesis method is proposed. First, the equivalent higher-order matrix of the system is developed using a set of linearly independent vectors to capture the effects of the neglected higher-order modes. Second, the perturbation method is applied to derive the change for both eigenvalues and eigenvectors of each component while implementing a modification to the updated finite element model. The perturbation for both the eigenvalues and eigenvectors of each component are used to formulate the synthesis equations containing the perturbation expression. Next, the model-updating process is conducted using the synthesis model for which the degrees of freedom have been greatly reduced. The reduction in the total degree of freedom speeds up the solution process for the model-updating problem. Finally, the computational efficiency and accuracy of the presented method is demonstrated using a wing structure and by modal testing of a bolted plate.